Kinerja Konseling Dalam Budaya Pendidikan Karakter Kedisiplinan : (Evaluasi Model Program Discrepancy pada Pondok Pesantren Darul Ma’rifat Kediri) - Luneto, Buhari; H. Abas, Abdul Kadir (Al-Minhaj : Jurnal Pendidikan Islam, 2019)
Counseling is a major component of guidance and counseling services. The importance of this counseling program, of course, requires an effort to assess the success of the counseling program. One way is to carry out an evaluation. The type of evaluation that can be used is the discrepancy model evaluation. This study uses a literature study design. This study presents a scientific idea of ​​a program evaluation model, namely a discrepancy model through secondary data sources, such as journals and books. The results of the literature study concluded that the purpose of the discrepancy model evaluation was to describe the gap between the realities of the performance of professional counselors in implementing guidance and counseling programs in schools with standards. In addition, it is also decision-oriented to assist counselors in making counseling program decisions. This study focuses on the evaluation of the implementation of disciplinary character education at the Darul Ma'rifat Islamic Boarding School Kediri. This research was conducted using a descriptive qualitative approach in a non-conformity evaluation model that presents several problems naturally and objectively in the field, which then analyzes the data based on inductive qualitative. This analysis concludes that: 1) The implementation of character education at the Darul Ma'rifat Kediri Islamic Boarding School is based more on the formulation of objectives rather than the pesantren itself which is then applied through the discipline of students in daily life. 2) The effectiveness of the implementation of character education can be assessed from the structure of the disciplines applied in this institution by going through several groupings or stratifications which are then implemented effectively.